The curious case of Neotroglocarcinus dawydoffi (Decapoda, Cryptochiridae): Unforeseen biogeographic patterns resulting from isolation - Van Der Meij, S; Reijnen, B (Taylor and Francis, 2014)
Coral gall crabs form a commonly overlooked component of the associated fauna of shallow-water reef corals and therefore little is known about their ecology and biogeography. This study investigated the biogeography and phylogenetic position of the informal Detocarcini species group within the Cryptochiridae. We used molecular data for two mitochondrial markers (COI and 16S) obtained from gall crabs covering (part of) a wide geographic range: the Red Sea, Malaysia, Indonesia and New Caledonia. Our phylogeny reconstructions portrayed the Detocarcini as paraphyletic within the monophyletic Cryptochiridae. A phylogeographic clustering was noticed in Neotroglocarcinus dawydoffi that was absent in its sister species, N. hongkongensis, and the closely related species Pseudocryptochirus viridis. A Neighbour Network was estimated for the N. dawydoffi dataset to visualize the similarity between sequences from different biogeographic areas, resulting in three groupings: (1) New Caledonia with Lembeh/Ternate (eastern Indonesia), (2) Semporna/Kudat (eastern Malaysia), and (3) Red Sea (Saudi Arabia). Cryptic speciation rather than isolation is discussed and rejected as an alternative explanation for the observed biogeographic pattern.